Таълим жараёнида талабаларни ҳаёт фаолияти хавфсизлигига тайёрлаш методик тизимни амалга ошириш босқичлари (SCIENCE and SOCIETY, 2023)
The article discusses the teaching methodology of life safety in vocational training. There are also the author investi- gates stages of information presentation in teaching .